2005
DOI: 10.1021/ja056092f
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioseletive Biginelli Reaction Using a New Chiral Ytterbium Catalyst:  Asymmetric Synthesis of Dihydropyrimidines

Abstract: The highly enantioselective three-component Biginelli condensation catalyzed by a recyclable chiral ytterbium triflate with a novel hexadentate amine phenol ligand containing a pyridyl group has been developed. A wide range of optically active dihydropyrimidines with remarkable pharmacological interest was obtained in high yields with good to excellent enantioselectivities under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(126 citation statements)
references
References 24 publications
1
124
0
1
Order By: Relevance
“…More significantly, in 2005, was reported the first highly enantioselective multicomponent Biginelli reaction using a recyclable ytterbium triflate coordinated with a novel chiral hexadentate ligand 147 bearing tertiary amine, phenol, and pyridine functional groups (Scheme 57). 116 The desired heterocycles 148 were obtained in high yields with enantiomeric excesses up to 99%. But the crucial advance was the discovery of the organocatalyzed enantioselective version of the Biginelli reaction in 2006.…”
Section: Enantioselective Multicomponent Reactionsmentioning
confidence: 99%
“…More significantly, in 2005, was reported the first highly enantioselective multicomponent Biginelli reaction using a recyclable ytterbium triflate coordinated with a novel chiral hexadentate ligand 147 bearing tertiary amine, phenol, and pyridine functional groups (Scheme 57). 116 The desired heterocycles 148 were obtained in high yields with enantiomeric excesses up to 99%. But the crucial advance was the discovery of the organocatalyzed enantioselective version of the Biginelli reaction in 2006.…”
Section: Enantioselective Multicomponent Reactionsmentioning
confidence: 99%
“…539 Catalytic amount of chiral organocatalyst based on chiral Binaphthol-derived phosphoric acid 93, 97, 98 leading to dihydropyrimidines with enantiomeric excess. …”
Section: Scheme 54mentioning
confidence: 99%
“…Several enantioselective synthetic protocols have been developed over the years. One of the first, was reported by Zhu and coworkers in 2005, 4 over one-hundred years after discovery of the Biginelli reaction. Zhu found that the use of a chiral ytterbium catalyst allowed dihydropyrimidines to be obtained in high yields and excellent enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this and in order to further enhance the chiral catalyst (-)-4,5-dimethyl-3,6-bis(o-tolyl)-1,2-benzenedisulfonimide (1; Figure 2) which is an efficient Brønsted acid chiral catalyst in Strecker 9a and Mannich reactions, 9b we herein report our studies into enantioselective, green Biginelli reactions between aromatic aldehydes 2, thiourea (3a) or urea (3b) and ethyl acetoacetate (4) carried out in the presence of chiral catalyst 1 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%